Using the PEST-analysis method to determine the impact of risk factors on the educational activities of a higher learning institution - Volivach, A.; Khimicheva, G. (Problems of Engineer-Pedagogical Education, 2019)
The topicality of the research lies in the urgency to improve the quality and competitiveness of higher learning institutions in the educational service market, and to determine the impact of the external and internal factors which condition the emergence of risks in the teaching and learning process. The purpose of the work is to use the PEST-analysis method to assess qualitative and quantitative characteristics of educational activities of higher learning institutions. To achieve this goal, the following tasks have been set: to make matrix tables of PEST-analysis, to carry out the analysis on the results obtained, and to develop organizational and technical measures to improve the efficiency and effectiveness of the performance of higher educational institutions. During the study, expert methods have been used to assess the probability of negative situations (risks) that affect the activity of higher educational institutions. This approach has made it possible to determine the priority level of every factor which might influence the activity of higher educational establishments, in particular Kyiv National University of Technologies and Design (KNUTD), and to develop recommendations for reducing any possible impact. The results of the study allow increasing the stability of any higher learning institution under uncertain conditions of the educational environment and are recommended for evaluating its activities during the QMS development according to the requirements of the international standard DSTU ISO 9001:2015.